Klippel-Trenaunay-Weber Syndrome. Case Report and Literature Review - Laura Vázquez Pis; Maday González Hernández; Aimé Marrero Gil; Antonio Mazot Rangel (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Klippel-Trenaunay-Weber syndrome is a rare congenital vascular malformation. Its characterized by a triad of clinical manifestations that includes venular, lymphatic, and venous vascular malformation, together with skeletal hypertrophy, soft tissue enlargement of one or more limbs, and presence of arteriovenous fistulas. We present the case of a 5-year-old girl who was confirmed by clinical and imaging findings to have Klippel-Trenaunay-Weber syndrome. This is a rare, infrequent disease with a not well-defined genetic inheritance pattern that requires multidisciplinary management. The treatment of choice is the symptomatic clinic, focused on avoiding disability, improving functional capacity, quality of life and preventing complications. The case is presented due to the infrequent nature of this condition to show its follow-up and also for teaching purpose.